2021
DOI: 10.1111/ggr.12383
|View full text |Cite
|
Sign up to set email alerts
|

A Method for Secondary Ion Mass Spectrometry Measurement of Lithium Isotopes in Garnet: The Utility of Glass Reference Materials

Abstract: We present a novel method for the measurement of lithium isotopes in garnet utilising glass reference materials and secondary ion mass spectrometry (SIMS). Measured lithium isotopic compositions of natural garnets are heterogeneous, making them unreliable reference materials for in situ determination. However, SIMS lithium isotope measurements of glasses derived from these natural garnets are isotopically identical to their parent garnets and more homogeneous, demonstrating that they can be used as reliable re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…In our garnets, Alm and Sps are inversely correlated, so the dominant matrix effects could cancel each other out to some extent (Hoover et al, 2021). On the other hand, if changes in δ 7 Li occur in regions where matrix chemistry is less variable, the Li-isotope variation cannot be entirely attributed to matrix effects where matrix chemistry change is unidirectional.…”
Section: Methodsmentioning
confidence: 86%
See 1 more Smart Citation
“…In our garnets, Alm and Sps are inversely correlated, so the dominant matrix effects could cancel each other out to some extent (Hoover et al, 2021). On the other hand, if changes in δ 7 Li occur in regions where matrix chemistry is less variable, the Li-isotope variation cannot be entirely attributed to matrix effects where matrix chemistry change is unidirectional.…”
Section: Methodsmentioning
confidence: 86%
“…Instrumental mass fractionation involving matrix effects has been known to occur for Li isotope measurements using SIMS (e.g., Bell et al, 2009;Kunihiro et al, 2019;Hoover et al, 2021). Therefore, we examined the matrix effects relative to a working standard garnet based on the isotope measurements of reference garnets with certain compositional characteristics.…”
Section: Methodsmentioning
confidence: 99%
“…Because of a lack of reference garnets with high Alm-component that cover the range of the Alm components of garnets in the unknowns, the relative matrix effect for garnets in unknown samples must be estimated by extrapolation of the correlation obtained. Previous studies have also suggested a positive correlation of the matrix effect with iron-endmember components such as the fayalite component in olivine (Bell et al, 2009;Kunihiro et al, 2019) and Alm component in garnet (Hoover et al, 2021). Then, we evaluated an impact of the correction in two domains with Alm from 0.45 to 0.65 and Alm from 0.65 to 0.8 that are typical compositions of core and rim of the garnets in unknown samples.…”
Section: Methodsmentioning
confidence: 99%
“…We have not examined the matrix effect incorporating the spessartine component (Sps = Mn/(Ca + Fe + Mn + Mg)) because of a lack of reference garnets that cover the range of the Sps components (0.01~0.32) of garnets in unknown samples. Hoover et al (2021) have suggested that the matrix effect related to the high Sps-component (Sps ~ 0.3) was also significant (~ 4‰) based on the Li isotope measurements using synthesized custom-made glass reference materials, but not on natural garnets. Their data indicate that the matrix effect is not clearly distinguishable from their analytical uncertainties estimated based on reproducibility precision (0.1 ~ 2.0‰ in 2s) for their glass reference materials with the variation in Sps less than 0.1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation